Synthesis and Thermotropic Properties of Some New Schiff Bases, N-[4-(4-n-Alkanoyloxybenzoyloxy)-2-Hydroxybenzylidene]-4-Cyano-, 4-Hydroxy-, 4-Thio- and 4-Nitroanilines - Sie-Tiong Ha; Guan-Yeow Yeap; Peng-Lim Boey (E-Journal of Chemistry)
A series of elongated Schiff base esters containing three aromatic rings with hexadecanoyl chain as one of the terminal group and various R substituents (R = CN, OH, SH, and NO2) at the other end of molecule were prepared, and their structures were confirmed via physical measurement. The thermotropic properties of these compounds were investigated via differential scanning calorimetry and polarizing optical microscopy. The thermal data indicate that all of these compounds exhibit mesomorphic properties. Whilst compounds with R = OH, SH and NO2 show nematic phases, compound containing cyano substituent are smectogenic in nature.